Perceptions of managers in the South African mobile industry regarding strategic sourcing benefits - Motsoeneng, Thapelo Samuel (My University, 2017)
In order to run a functional business, companies form relationships with other entities that exist within their supply chain. These relationships have implications to the company in terms of their financial as well as operational efficiencies. In practical terms, the relationships formed with third party companies are entered into using, in most cases, the procurement system of a company. Given that the procurement system impacts the outflow of funds in terms of costs paid to suppliers as well as the “last mile” that these suppliers play a role in; it is necessary for companies to apply their minds to how they ensure efficiency in the manner in which they carry procurement out. The centrality of the procurement function within a company implies that it is a pivot on which company operations rotate. Seeing this pervasive presence of the procurement function throughout the units of a company, the attainment of company strategic goals relies on a well-functioning procurement system. Strategic sourcing is a component of the procurement function that gives practical expression to the strategy within the broader strategic approach of a company. This article explores the perceptions of managers within the mobile phone industry on the manner in which Mobile Network Operators utilize strategic sourcing in order to ensure that they stay in business and become significant players within their industry. The paper explores the following propositions; Proposition 1: Strategic sourcing contributes to company performance. Proposition 2: Strategic sourcing can be used to achieve cost reduction. Proposition 3: Strategic sourcing can be used to gain and maintain competitive advantage. Proposition 4: Strategic sourcing is a structured process. Proposition 5: Supplier development initiatives are an important component of strategic sourcing 9 In this exploration endeavour, a strategic sourcing model was selected and its elements were used to develop a tool to analyse the benefits of strategic sourcing on company performance, cost reduction and competitive advantage.
MBA
Keywords: Executives -- South Africa. Executive ability. Mobile communication systems -- South Africa.